Engaging in Earnings Management to Avoid Negative Earnings - Subekti, Imam (Jurnal Akuntansi Multiparadigma, 2010)
The purpose of this study is to investigate the earnings management behavior of companies listed in the Indonesia Stock Exchange (ISE). Specifically, the study investigates whether companies engaging in real earnings management or accrual management intent to avoid negative earnings; it also examines whether earnings management behavior supports efficient contracting or opportunistic behavior perspective. The sample of this study comprised 166 firm-years of manufacturing industrial sector during the period 2004 â 2005. Using multiple regressions, the study finds evidence that the companies engage in both earnings management, which are discretionary expenses (proxy of real earnings management) and accruals management. This evidence supports the studies of Graham, Harvey, & Rajgopal (2005) and Roychowdhury (2006). Â Another result shows that the real earnings management conducted by the companies is efficient partially, while the accruals management is opportunistic.